PENGEMBANGAN PERANGKAT PEMBELAJARAN PENEMUAN TERBIMBING BERBANTUAN MIKROSKOP SEDERHANA UNTUK MELATIHKAN KETERAMPILAN PROSES SAINS DAN PEMAHAMAN KONSEP MATERI SISTEM ORGANISASI KEHIDUPAN PADA SISWA SMP - Hartanti, Indah; Raharjo, Raharjo; Purnomo, Tarzan (Universitas Negeri Surabaya, 2017)
This study aims to produce science instructional sets Guided Discovery Model Assisted Microscope Simple to facilitate science process skills and students’ understanding concepts. The instructional sets developed are Syllabus, Lesson Plans, Worksheets, Simple Microscope Media, Science Process Skills Test, and Concepts Understanding Test. This type of research is the instructional sets development research. The instructional sets development model used is the instructional sets development of 4D Model. The experiment of instructional sets was conducted at SMP Negeri 2 Losari Brebes by using One Group Pretest-Posttest Design. The instruments used in this study were the validation sheets of instructional sets, the observation sheets of the implementation of Lesson Plans, the students’ activities, the assessment sheets of science process skills and concepts understanding, the observation sheets of attitude and the questionnaires. Data analyzing technique used were descriptive analysis of quantitative and qualitative. The result of this research shows that the instructional sets developed are valid and can be used. The implementation of instruction are 100% done with very good category done. The most dominant of students’ activity is doing observation/investigation using simple microscope. Science process skills and students’ concepts understanding increases by value of N-Gain at middle category. The positive response of students towards the instruction is 86% with very strong category. Based on the results of data analysis, it can be concluded that the instructional sets with Guided Discovery Assisted Simple Microscope are feasible (valid, practical, and effective) to use to facilitate science process skills and students’ concepts understanding